IMPLEMENTASI PELAYANAN TERPADU SECARA ELEKTRONIK YANG DISELENGGARAKAN OLEH KANTOR BADAN PERTAHANAN NASIONAL KOTA ADMINISTRASI JAKARTA UTARA (STUDI BADAN PERTANAHAN NASIONAL KOTA ADMINISTRASI JAKARTA UTARA) - Maysarah Maysarah (Jurnal Abdi Ilmu, 2022)
This study seeks to analyze the process of embodiment and electronic/online services at the Ministry of ATR/BPN, as well as data conditions and strategies for preparing land data towards valid electronic/online data services which are needed for legal certainty for land rights owners and for making strategic decisions in National level. In this study, researchers used qualitative research methods. This research is located and has an object at the National Land Agency (BPN) of North Jakarta City Administration, and other agencies involved in connection with this research, the Ministry of Law and Human Rights, for the Heritage Center or the so-called DITJEN AHU and the Regional Development Tax and Ritribution Service Unit (UPPPD). Taman Sari and the Regional Development Tax and Ritribution Service Unit (UPPPD), which is a valid requirement for a request for transfer of rights at the National Land Agency (BPN) of North Jakarta City Administration, while the research period is 1 year. In selecting a qualitative research sample, the data source sample is selected purposively and is snowball sampling. Based on the results and discussion of the Land Data Readiness research towards Electronic/Online Services, it can be concluded as follows: (1) The Regulation of the Minister of Agrarian Affairs and Spatial Planning/Head of BPN RI Number 5 of 2017 concerning Electronic Land Information Services has not been implemented in its entirety. The implementation of these regulations is hampered by the content in the regulations that are not yet in line with other regulations governing the same thing. The lack of socialization, communication, and resources related to the implementation of regulations makes many Land Offices tend to have a negative response and are less concerned about the existence of online service programs, although there are also Land Offices that act in harmony with the substance of online services; (2) The readiness of land data for online services has not yet reached 100%. (3) Strategies for implementing and preparing land data for electronic services that can be carried out (4) The implementation of Presidential Regulation Number 95 of 2018 concerning the Electronic-Based Government System (SPBE), is constrained due to the Regional Development Tax and Ritribution Service Unit (UPPPD) of Tamansari District and the Regional Development Tax and Ritribution Service Unit (UPPPS) of Penjaringan District, so that Validation takes a long time, and if there is a request for a reduction in Duties on the acquisition of Land and Building Rights (BPHTB), it is not systematically granted.